MIE-BIN: Innovation of noodles from Madeira vine leaves (Anredera cordifolia [Ten.] Steenis) as a strategy for functional food diversification in supporting balanced nutrition fulfillment - Azrial, Fahmi; Sahdan, Fahrizal; Putri, Okta Angelia; Afrida, Febrian; Listiana, Ika (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In Indonesia, the nutritional situation is still concerning with the prevalence of stunting in children under five reaching 30.8%. Indonesia's rich biodiversity, especially local plants such as binahong (Anredera cordifolia [Ten.] Steenis) offers great potential as an innovative solution to overcome nutritional problems. This research focuses on developing binahong-based noodles (MIE-BIN) as a quality local food diversification strategy with the aim of making a real contribution to fulfilling balanced nutrition and supporting national food security through a comprehensive approach that combines aspects of nutrition, food technology, and local plant potential. Methods: This research was conducted through a descriptive analytical literature review with a qualitative approach. This study employed a systematic literature search of primary sources (scientific journals, conference proceedings, research reports, and reference books) and secondary sources (official statistics, policy documents, and government publications) from 2014–2024 to analyze the potential of binahong leaves as a noodle ingredient. Findings: The findings show that Binahong Noodles (MIE-BIN) have superior nutritional, textural, sensory, and functional properties compared to conventional noodles, offering high protein, fiber, antioxidants, and bioactive compounds with significant health benefits, while also presenting strong potential for diversification, food security, and sustainable community nutrition. Conclusion: This innovation shows significant potential in supporting metabolic health through bioactive compounds such as flavonoids and saponins that can reduce the risk of chronic diseases. Novelty/Originality of this article: Through modern food technology and innovative approaches, MIE-BIN not only offers solutions for local food diversification, but also has the potential to become a strategic instrument in nutritional interventions, utilization of local resources, and improving the quality of life of the community.